Shear-Induced Pathway of Platelet Function in Cardiac Surgery - Tabuchi, Noriyuki; Tigchelaar, Izaak; Van Oeveren, Willem (Seminars in Thrombosis and Hemostasis, 1995)
The contribution of platelet dysfunction to the impaired hemostasis after cardiac surgery remains to be established, because there is no sensitive method to assess platelet function. Measurement of the shear-induced pathway of platelet function, an important mechanism in inducing hemostasis, became possible by a novel shear-inducing technique, the in-vitro bleeding test (Thrombostat 4000). By using this test, the changes in platelet function during cardiopulmonary bypass and their contribution to hemostasis were investigated in patients undergoing cardiac surgery. Platelet function is quickly impaired shortly after the start of cardiopulmonary bypass, and partly recovered at the end of cardiopulmonary bypass. The function of aspirin-treated platelets is more severely affected than of nonaspirin platelets during cardiopulmonary bypass. Furthermore, the degree of platelet dysfunction at the end of the operation, but neither the platelet number nor the activated clotting time, was significantly correlated with blood loss from the chest drain after cardiac surgery. These results indicate the significant and variable effects of cardiopulmonary bypass on the shear-induced pathway of platelet function. Moreover, the impairment of this function of platelets appears to be a major cause of excessive bleeding in patients after cardiac surgery. Therefore, the routine use of the shear-inducing test seems helpful to make a proper diagnosis and design the therapy for bleeders after cardiac surgery.
Keywords: cardiopulmonary bypass; cardiac surgery; hemostasis; platelet function; shear-stress; Thrombostat